From Responding to Uncertainties and Ambiguities to More Constructive and Inclusive Debates on Commercial Sex and Sex Trafficking. Issue 3 (3rd April 2023) - de Vries, Ieke; Reid, Joan A.; Farrell, Amy
ABSTRACT: Commercial sex policies are often at the core of many anti-trafficking efforts, yet rigorous empirical evidence about the effectiveness of these policies in preventing sex trafficking is lacking. In response to ongoing debates about which commercial sex laws and policies would help prevent sex trafficking, we seek to contribute to more nuanced discussions on commercial sex policies in relation to sex trafficking victimizations. The purpose of this essay is to identify the pitfalls in the debate on how to govern commercial sex markets, emphasizing 1) the lack of recognition of the variation in laws and policies on commercial sex; 2) the moral instead of empirical underpinnings of the debate; 3) ambiguous and stigmatizing notions of vulnerability to sex trafficking victimizations; and 4) a continued reliance on a traditional criminal justice system response that may cause harm to victims. We conclude with five premises to promote more nuanced, inclusive, and collaborative debates and governance of commercial sex markets that allow countries and local jurisdictions to move away from response models for which harm-reducing effects are either unknown or refuted.